Perspectives on Sexual Health Among Women Who Underwent Pelvic Radiation Therapy: A Qualitative Analysis. (1st August 2022) - Morgan, O; Schnur, J; Caban-Martinez, A; Duenas-Lopez, M; Huang, M; Portelance, L; Marshall, D
ABSTRACT: Introduction: Impaired sexual function significantly decreases quality of life in female survivors of pelvic cancer who receive radiation therapy (RT). The literature estimates that 40-100% of gynecologic cancer survivors and 18-59% of rectal cancer survivors experience sexual dysfunction. Despite this prevalence, many patients report being insufficiently informed before treatment about potential sexual side effects of RT. Objective: The primary goal of the present study was to understand patients' perceptions of how prepared they felt for the presence of sexual toxicity after RT, how informed they felt about sexual toxicity management approaches, and what they would have liked to have known before beginning RT treatment. Methods: Semi-structured interviews, in English and Spanish, were conducted with 20 women who received radiation to the pelvis as part of cancer care treatment. Patients responded to advertisements or were referred by providers. All interviews were conducted virtually by two medical students between June - October 2021. Thematic analysis was conducted using NVivo. Patients also completed an online demographics survey on REDCap. Results: We identified four primary themes: 1) "I'm not a woman anymore" - all respondents felt these side effects had a negative impact on their life, including lower self esteem and no longer feeling sexy, nor like a woman. The women who were not properly informed about their side effects felt blindsided and embarrassed about their symptoms, 2) "Past sexuality influences current information preferences" - The unique experiences each woman had with sexual activity before undergoing RT impacted on how much they wanted to discuss sexual toxicity with their radiation oncologist. Yet nearly across the board, participants did want their doctor to be the one to initiate the discussion; 3) "When the internet is more useful than my providers" - many patients reported turning to the internet rather than their doctors for answers once they began experiencing symptoms if the symptoms had not been discussed with their doctor a priori, and found both information, normalization, and community online; 4) "Setting accurate expectations is key" - The women who were properly informed about sexual dysfunction expressed gratitude, and felt that while the sexual dysfunction was physically difficult, they were not surprised or frightened by the side effects and reported that this was psychologically helpful. Conclusions: The results indicate that patients want physicians to initiate conversations about sexual function and to provide significantly more information about sexual dysfunction prior to RT. They also want radiation oncologists to be more active and directive in providing concrete symptom management strategies. Participants emphasized the importance of taking a thorough sexual history early on in the clinical encounter in order to monitor sexual dysfunction and to identify individual patient priorities surrounding sex and quality of life post treatment. Patients might also benefit from suggestions of online communities where sexual issues are discussed openly and productively. Overall, these findings provide radiation oncology providers with important information about patients' unmet sexual information needs prior to RT, and patient preferences for how to help them feel more prepared and less distressed when sexual dysfunction occurs. Disclosure: No